Multi-Carrier Differential Chaos Shift Keying Modulation with Permutation Index - Guo, Qin; Chen, Pingping; Fang, Yi; Lin, Zhijian; Chen, Feng (2022 IEEE/CIC International Conference on Communications in China (ICCC), 2022)
This paper proposes a multi-carrier differential chaos shift keying modulation using permutation index (PI-MC-DCSK) over multipath fading and additive white Gaussian noise (AWGN) channels, by exploiting the advantages of permutation index and multi-carrier modulations. In the proposed PI-MC-DCSK, the predefined subcarriers, can carry multiple bits associated with the order of permutation index, which can achieve high energy efficiency as compared to the one bit carried by each subcarrier in the conventional MC-DCSK. At the transmitter, the first predefined subcarrier stores reference data, while the rest carry data signal. Then, the transmission energy of the system can be significantly saved. At the receiver, received data passes through the multi-carrier demodulator, and the mapped bits are estimated by the correlators. Simulation results show that the proposed PI-MC-DCSK has excellent error performance and provides a much higher data rate than the conventional MC-DCSK.